(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Biomedical waste management has become a critical environmental and public health challenge due to the rapid increase in hazardous waste generated by hospitals, diagnostic laboratories, and rural healthcare centres. Inefficient monitoring and delayed waste collection often result in waste overflow, infectious disease transmission, hazardous gas emissions, and increased occupational health risks. Despite the availability of conventional waste management practices, there remains a significant research gap in the development of low-cost, real-time, and intelligent monitoring systems suitable for resource-constrained healthcare facilities. This study aims to design, model, implement, and validate an intelligent biomedical waste monitoring system based on the Arduino Uno microcontroller integrated with an Android mobile application. The proposed system utilizes ultrasonic sensors for waste level measurement, MQ-135 gas sensors for hazardous gas detection, and Bluetooth communication for real-time wireless monitoring. Mathematical models for ultrasonic distance estimation and gas concentration calibration are developed, and the system performance is evaluated through experimental analysis using metrics such as alert accuracy, response time, power consumption, and waste collection efficiency. Experimental results demonstrate that the proposed system significantly improves operational efficiency, minimizes waste overflow incidents, enhances safety compliance, and reduces manual monitoring requirements compared with conventional waste collection methods. The developed framework provides a scalable, reliable, and cost-effective solution for intelligent biomedical waste management, offering substantial potential for deployment in hospitals, clinics, and rural healthcare facilities, particularly in resource-limited settings.